Nivel de conocimientos del profesional de enfermería y su actitud ética en el cuidado del paciente del Hospital Leoncio Prado de Huamachuco - Flores Roldán, Santos Elizabeth (2016)
This descriptive correlational, cross-sectional research was conducted in order to identify the knowledge and ethical attitude of professional ethics nursing working in the Leoncio Prado Hospital of Huamachuco. The sample consisted of 20 care nurses. For data collection we used two instruments survey to measure the level of knowledge and the survey of ethical attitude of nursing. The information collected was processed and tabulated in SPSS FOR Windows version 22 statical tests used chi – square. The findings are: 50 % of nurses have a high level of knowledge on Ethics and 65 % have a proper ethical attitude in patient care , finding that there is a statistically significant relationship between the level of knowledge and the attitudes (p=0.019).